Digital Storytime: Investigating Prathambooks.org's Role in Reducing College Reading Anxiety - Marlina, Leni; Safitri, Dian; Amri, Zul; Aufa, Fauzul; Yuliani (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
EFL learners consider reading English texts as a tiresome and unpleasant task that must be completed since they are not used to being exposed to interesting reading materials (Lee, 2015, p. 66). Digital children’s literature allows EFL learners to experience reading books interactively. This research aims to investigate whether using digital children’s literature prathambooks.org has a significant effect on EFL college students’ reading anxiety. prathambooks.org is a web-based story book that provides an open-access repository through the prathambooks.org feature. This study examined 184 undergraduate students enrolled in Introduction to Literature at Universitas Negeri Padang's English Department during the 2022/2023 academic year. Data were collected via a 26-item reading anxiety questionnaire adapted from Ahmad et al. (2013), administered pre- and post-intervention. The intervention consisted of a 15-day program utilizing 15 digital stories from Prathambooks.org, supplemented with comprehension and vocabulary exercises. This protocol was designed to investigate the effects of digital children's literature on college-level reading anxiety. The finding showed a positive effect on students’ reading anxiety after following reading treatment. The students’ post-response scores decreased significantly by about 4.04%, from 70.51% to 66.47%. This research proves that integrating prathambooks.org with structured exercises as reading material has a significant effect on decreasing EFL college students’ reading anxiety.